What constitutes a histological confirmation of cancer? A survey of terminology interpretation in two English regions. Issue 3 (1st March 2001) - Silcocks, P; Page, M
Abstract : Aims —To compare interpretation by cancer registries and histopathologists of phrases that might confirm a diagnosis of cancer. Methods —One hundred and thirty one consultant pathologists were sent a questionnaire containing 37 phrases used in pathology reports, including those indicating cancer and those not. Pathologists were asked to indicate whether each phrase confirmed the disease, ruled it out, or was uncertain, together with a subjective estimate of how frequently they used the phrase. Results —There was a 58% response rate with similar interpretation between regions. There were some differences in frequency of use. At least 50% of respondents considered 12 terms as confirmatory (for nine the lower 95% confidence limit was greater than 66%). Conclusions —The registry should consider ignoring four of the 13 terms currently regarded as confirmatory. Terminology used in pathology reports should be standardised across registries. Registries and coding departments should use empirical evidence to assess which phrases confirm a diagnosis.